Maternidade para mães trabalhadoras: depressão pós-parto, stress, rede de apoio e conjugalidade - Manente, Milena Valelongo [UNESP] (2014)
The transition period of pregnancy and post partum, bring some transformation to the life of the woman. If, additionally the mother works outside some adjustments will be necessary to the parents, in order to guarantee their emotional health. The present research aimed to show how worker women report their feelings about pregnancy, parturition and motherhood, describing their emotional and conjugal status, professional life and support available. Besides obtaining social demographic information from the mothers, the study has also made an association among the depression/stress and 27 variables concerning care. A total of 30 worker women, first-baby -mothers, with babies from two to six months of age, took part of this study. The instruments employed for the emotional evaluation of the mothers were: Edinburgh Postnatal Depression Scale and Lipp Stress symptoms Inventory for Adults. For the social demographic collection and information about care, and inventory was applied, comprising the following: pregnancy history, perinatal, puerperium, motherhood and support available, conjugal satisfaction and motherhood and motherhood and occupation life. The percentage of mothers, with sumptoms of depression was 13,3% and stress was 43,3% wih predominance for the resistance phase and psychological symptoms. Among the socio-demographic variables studied, it was observed the presence of protective factors, during the transition. The mothers were pleased with the support available during pregnancy, representating 90% and 97% were happy with the conjugal status. The same mothers took part in pregnancy informative groups, equivalent to 53% of the sample. During puerperium the mothers felt supported, and the husband helped with taks concerning the baby in 77% of the sample. The study has also detected lack of access to information about breastfeeding for 60% of the mothers, and exclusive breasfeeding on the first six months of age only 30% of the sample...